Analysis of Promise as a Speech Act in the Light of Satyajit Ray’s Cinema - Dipanwita Das; Pallab Sur (CV. Tirta Pustaka Press, 2025)
The current study is focusing on the analysis of promise as a speech act from a pragmatic and stylistic point of view, in correlation with Austin's speech act theory, specifically based on the instances of promises from the screenplays of Satyajit Ray’s three greatest masterpieces - his debut film, “Pather Panchali”, “Apur Sansar”, which is the third and last instalment of “Apu Trilogy:, and